Junctures in women's leadership : the arts - Brodsky, Judith K.; Olin, Ferris (Junctures (New Brunswick, N.J.), 2018)
"In this third volume of the series Junctures: Case Studies in Women's Leadership, Judith K. Brodsky and Ferris Olin profile female leaders in music, theater, dance, and visual art. The diverse women included in Junctures in Women's Leadership: The Arts have made their mark by serving as executives or founders of art organizations, by working as activists to support the arts, or by challenging stereotypes about women in the arts. The contributors explore several important themes, such as the role of feminist leadership in changing cultural values regarding inclusivity and gender parity, as well as the feminization of the arts and the power of the arts as cultural institutions"--